Morphodynamics in the Confluence of large regulated Rivers: the case of Paraná and Paranapanema Rivers - José C. Stevaux; Renato J. Paes; André Amâncio Franco; Mário L. de C. Etchebehere; Rafaela Harumi Fujita (Latin American Journal of Sedimentology and Basin Analysis, 2009)
The confluence of the Paraná and Paranapanema Rivers is studied according to morphology and dynamics. It is probably the only example of this type of fluvial environment involving a large, tropical and intensive regulated river. Confluence channels were monitored along a hydrological cycle (high-low water level) in terms of morphology, flow velocity, magnitude, structure, and bedload dynamics. In this case, hydrology is controlled by the flow of the tributary, which develops a continuous and well-defined thalweg since the collector channel (a secondary channel of the Paraná River) that presents relatively large bedforms that reduce stream power by increasing roughness. Although significant differences in channel morphology were not observed along the hydrological year, bed material texture indicates that the channel bottom is suffering a slight armoring process. This is probably the reason for the large asymmetry of channel confluence where the depth of the tributary channel is larger than that of the main collector channel (the Paraná left branch). The Rosana Dam, closed in 1987 and located 26 km upstream from the confluence, is the cause of the changes in sediment transport and the generation of the channel pavement. With the closing of the Porto Primavera Dam (2000) in the Paraná River (27 km upstream from the confluence) a new morphodynamics is foreseen for this environment, and this paper can be seen a relevant pioneer reference for environmental monitoring and management. A morfologia da confluência de rios intensamente regulados de grande porte é estudada tendo como exemplo a confluência dos rios Paraná e Paranapanema. Para este trabalho foi realizado o levantamento batimétrico de detalhe em dois períodos do ciclo hidrológico (cheia e vazante), a velocidade e estrutura da corrente e o tipo da carga de fundo. A hidrodinâmica da confluência é controlada pelo rio tributário, que desenvolve um talvegue bem definido e contínuo. O canal coletor (canal secundário do rio Paraná), uma vez que possui grande carga de fundo constituída de formas de leito de relativa expressão topográfica, tem sua potência de canal reduzida (aumento da rugosidade). Por outro lado a ausência de carga do rio Paranapanema propicia a formação de um canal mais fundo que o do Paraná. Muito embora não se tenha observado alterações significativas na morfologia dos canais entre os períodos de vazante e cheia, o mesmo não ocorreu com a textura da carga de fundo: o canal do tributário está sofrendo processo de ajoiamento (armoring effect) ligado ao fechamento da barragem de Rosana (1987). O trabalho é uma contribuição inovadora uma vez que estudos desta natureza foram apenas desenvolvidos em rios de pequeno porte, alem de apresentar dados importantes para subsidiar estudos da dinâmica de fluxo, da ecologia fluvial e para avaliar as alterações introduzidas pelos reservatórios em áreas de confluência.